Striated duct adenoma presenting with intra‐tumoral hematoma and papillary thyroid carcinoma‐like histology. Issue 6 (25th April 2017) - Ito, Yohei; Fujii, Kana; Murase, Takayuki; Saida, Kosuke; Okumura, Yoshihide; Takino, Hisashi; Masaki, Ayako; Beppu, Shintaro; Kawakita, Daisuke; Ijichi, Kei; Inagaki, Hiroshi
Abstract : Striated duct adenoma of the salivary gland is a rare benign tumor characterized by unilayered duct epithelium and striations of the tumor cell membranes. To the best of our knowledge, only six cases have been reported in the literature. Here we report an additional case, which was complicated by an intra‐tumoral hematoma on clinical presentation and by papillary thyroid carcinoma‐like histology on intra‐operative frozen section diagnosis. An asymptomatic 78‐year‐old male presented with a two‐year‐history of a painless tumor of the left parotid. An intra‐tumoral hematoma, which is unusual for a salivary gland tumor, was suspected from results of pre‐operative radiology. The patient then underwent a left parotidectomy. The intra‐operative frozen section diagnosis indicated a benign tumor, although ectopic papillary thyroid carcinoma was raised as a differential diagnosis since the eosinophilic tumor cells occasionally possessed nuclear grooves and nuclear pseudo‐inclusions. By precise histopathological examination using paraffin sections, the tumor was finally diagnosed as striated duct adenoma. This type of tumor has unique features of hypervascular stroma and papillary thyroid carcinoma‐like nuclei. In our case, the former feature was associated with the intra‐tumoral hematoma and the latter feature, with difficulty in frozen section tumor diagnosis.